The Underground Economy in Times of Crisis: An Analysis of Undeclared Work in Europe. - Pérez-Magro, Mónica; Millán-Tapia, José María; Millán-Tapia, Ana; Román-Díaz, Concepción (Revista de Estudios Andaluces, 2017)
This study analyzes undeclared work as a key portion of the shadow economy in the EU-28, with special focus on its incidence, dynamics, structure, differences across countries and underlying determinants. To this end, linear regression and binary discrete choice models are applied to microdata drawn from 2 special Eurobarometers which are designed to explore undeclared work phenomenon in the years 2007 and 2013. Our results stress the importance of (i) the individual assessment of irregular and individualistic behaviours; (ii) the perceived risk of being detected undertaking paid undeclared work; (iii) the occupation; and (iv) the aggregated conditions, as determinants of undeclared work. The implications of these results for the existing policy options for dealing with the shadow economy are also discussed.